1989
DOI: 10.1515/hfsg.1989.43.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Lignin: A Photochemical Study of a Phenolic α-Carbonyl β—O—4 Lignin Model Dimer 4-Hy droxy-3-Methoxy-α- (2′-Methoxyphenoxy)-Acetophenone

Abstract: KeywordsLignin Photodegradation β-Ο-4 Lignin modcl compound Phenolic dimer Photochemical bond cleavage 5,5' -O-4Tetramer Frec-radicals α-Carbonyl-phenyl derivatives synthesis Bisulphite pulp (maritime pine) SummaryThe photoyellowing of bleached high yield wood pulp induced by lignin was studied using the title phenolic a-carbonyl -O-4 lignin model L Its photochemical reactivity was examined in both liquid (benzene and buffered aqueous ethanol) and solid (adsorbed on bleached chemical pulp) media and compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…[3] It has been shown that "essentially all" 5-5 linking motifsi nl ignin are actually found as part of the dibenzodioxocin linking motif ( Figure 6). [3] The 5-5 linking motif can be modelled using biphenyl-type compounds,w hich are generally synthesized via dimerization reactions using sodium or potassium persulfate/iron(II) sulfate mixtures [91,132] or K 3 Fe(CN) 6 [133,134] as shown in Scheme12. Alternatively,c ommercially available biphenyl or 2,2' biphenol are often used.…”
Section: -5/dibenzodioxocin-type Model Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] It has been shown that "essentially all" 5-5 linking motifsi nl ignin are actually found as part of the dibenzodioxocin linking motif ( Figure 6). [3] The 5-5 linking motif can be modelled using biphenyl-type compounds,w hich are generally synthesized via dimerization reactions using sodium or potassium persulfate/iron(II) sulfate mixtures [91,132] or K 3 Fe(CN) 6 [133,134] as shown in Scheme12. Alternatively,c ommercially available biphenyl or 2,2' biphenol are often used.…”
Section: -5/dibenzodioxocin-type Model Compoundsmentioning
confidence: 99%
“…Severals tepwise approaches begin with the synthesis of ad ifunctional, often as ymmetric 5-5 or a4 -O-5 motif, which can then be extended to as equentially symmetrical oligomer.T his approachh as been used to accesst etramers [132,146] As imilara pproachi st os ynthesize dimeric or trimeric sequences of linking motifs that are then subjected to radicald imerization reactions. This has been used to generate tetramers [147,148] with three linking motifs-(b-O-4) (5-5) (b-O-4) and (b-5) (5-5) (b-5)-and hexamers [149] These two related approaches can be very successful as they allow the swift building up of multi-linking motif model compounds in moderate-to-good overall yields.…”
Section: Stepwise Synthetic Approachesmentioning
confidence: 99%
“…Brought to you by | University of Queensland -UQ Library Authenticated Download Date | 6/20/15 9:13 PM Castellan et al (1989) have shown in their studies on lignin model compounds that the cleavage of a-carbonyl-ß-O-aryl ether linkages is one of the main pathways of photodegradation of lignin. Holmbom et al (1989) have provided evidence for the cleavage of acarbonyl-ß-O-arylether linkage, by means of GC/MS analysis of the extractives of photodegraded alkaline hydrogen peroxide bleached and unbleached spruce groundwood.…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…The objectives of this study are (1) to determine if spin trapping by phenyl tert-butylnitrone (PBN) can be used to intercept radicals initially formed such as 2 and 3 before radical rearrangements and (or) recombinations occur; (2) to study the properties of colored oligomers, which also form on photolysis of 1 (1)(2)(3), and (3) to synthesize a phenolic rearranged-recombination isomer of 1 and study how its free radical chemistry is related to colored oligomers and presumably to the photoyellowing of lignin itself. ated by radical reactions (8).…”
mentioning
confidence: 99%